Antiviral immune responses in mice deficient for both interleukin-2 and interleukin-4. - Bachmann, M; Schorle, H; Kühn, R; Müller, W; Hengartner, H; Zinkernagel, R; Horak, I (1995)
Antiviral immune responses of mice lacking interleukin-2 (IL-2) or IL-4 or both IL-2 and IL-4 (IL-2/4) were compared by using different viruses. Primary cytotoxic T-lymphocyte (CTL) responses against lymphocytic choriomeningitis virus (LCMV) were only moderately reduced in mice lacking IL-2 and were normal in mice lacking IL-4. Mice deficient in both interleukins exhibited variable and more strongly reduced but nevertheless in vivo protective LCMV-specific CTL responses. Similar results were obtained with vaccinia virus. Upon virus-specific restimulation in vitro, spleen cells from IL-2- and IL-2/4-deficient mice failed to generate CTL responses against virus-infected target cells, whereas the response of mice deficient in only IL-4 was comparable to that of control mice. The addition of IL-2 during in vitro restimulation completely restored the responses of both IL-2 and IL-2/4-deficient mice. T-helper-cell-independent immunoglobulin M and T-helper-cell-dependent immunoglobulin G antibody responses against vesicular stomatitis virus glycoprotein were within normal ranges for the various mutant mice. After LCMV infection, specific antibody responses against LCMV nucleoprotein were reduced four- to eightfold. These results show that mice lacking IL-2/4 have an overall tendency to exhibit more severely reduced CTL responses than IL-2- or IL-4-deficient mice. Nevertheless, and surprisingly, in vivo protective immune responses were mounted in the absence of IL-2/4, suggesting that besides a minor contribution from IL-4, other interleukins compensate in vivo for the lack of IL-2 in IL-2-deficient mice.